MOTIVATION OF SALES MARKETING EMPLOYEE WORK AT COMFORT HOTEL DUMAI - Tutut Dia Ambarani; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Responses in the world of tourism are the opinions or point of view of visitors and tourists in understanding a tourist destination. This research was conducted at the Comforta Hotel Dumai located at jl. jend. Sudirman no. 58, Dumai- Riau- Indonesia. This study aims to determine the responses of sales marketing employees at the Comforta Hotel Dumai. This study uses a Quantitative Descriptive method to process data obtained in the field through interviews, observations, questionnaires and documentation study all information collected and studied so that it becomes a complete unit (Sugiono. 2000). Whereas for the sample in the study as many as 3 respondents, the data collection techniques used were observation, interviews, questionnaires and documentation study using a likert scale as a measuring tool. Based on the results of research that has been done, the response of sales marketing employees at the Comforta Hotel Dumai with sub-variables of Physical Needs(86,6%), Security Needs (50,0%), Social Needs(90,0%), Appreciation Needs (66,6%) and Self-actualization Needs (83,3%) with good research conclusions. Keywords: Motivation, Sales marketing, Hotel